IMPROVING THE ABILITY OF READING SALAT USING THE READING ALOUD METHOD - Salim, Agus; Subando, Joko (Proceeding of International Conference of Islamic Education, 2023)
Abstract: By using the Aloud reading method, it allows students to be more interested in reciting Salat because reading includes the beautiful rhythms of the Al-Qur'an songs, with the hope that children will love the Al-Qur'an more. By loving the Qur'an, students will learn to read Salat in earnest, how to read Salat properly and correctly according to the rules of the science of tajwid. First, Aloud Reading Al Quran comes from the singing of the Arab ancestors. Second, Aloud Reading was inspired by the songs of infidel slaves who were prisoners of war. Both of these theories confirm that the smooth recitation of the Koran comes from traditional Arabic treasures (of course smelling of the desert). With this theory it is also emphasized that the songs of the Koran ideally have Arabic rhythms. The Aloud Reading Method is a way of presenting Salat reading learning materials to students by applying the fluency and memorization of the Qur'an aloud to improve reading skills. In this thesis discussed are research methods, place and time of research, research subjects, data collection techniques, data analysis, indicators of action success. Classroom action research is emancipatory and liberating because this research encourages freedom of thought and argument on the part of students, encourages teachers to experiment, research and use wisdom in making decisions or judgments. To obtain the necessary data in this study several data collection techniques were used, namely as follows: 1. Observation 2. Direct Test. Data analysis was directed to find out how much the Salat Reading Ability increased in class IV students of MIM Blabung Simo after being given action. Data analysis in this study used percentages, namely dividing the increase in the average score of ability, namely fluency and memorization of prayer readings by the average score before giving action and then multiplied by 100%.